2020
DOI: 10.1111/cas.14620
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of pseudogene UPAT leads to hepatocellular carcinoma progression and forms a positive feedback loop with ZEB1

Abstract: Hepatocellular carcinoma (HCC) is a common disease worldwide. Accumulating reports have evidenced the internal connection between epithelial‐mesenchymal transition (EMT) and cancer stem cells (CSCs), as well as their significance in metastasis and post–operative recurrence. In this study, we investigated an interesting ubiquitin‐proteasome pathway associated pseudogene of AOC4, also known as UPAT, and showed that it was downregulated in 39.78% (37/93) of patients with hepatitis B virus (HBV)‐related HCC. Downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…WFDC21P is lower expressed in carcinoma tissues than in paired paracarcinoma tissues, and its expression levels are decreased as HCC progresses [72]. AOC4P (UPAT) is downregulated in 39.78% of individuals with HBV-related HCC [73]. GOLGA2P10 is upregulated in HCC tissues and cells treated with ER stress inducers (tunicamycin and thapsigargin) [74].…”
Section: Cancers Located In the Abdomen And Bonesmentioning
confidence: 99%
“…WFDC21P is lower expressed in carcinoma tissues than in paired paracarcinoma tissues, and its expression levels are decreased as HCC progresses [72]. AOC4P (UPAT) is downregulated in 39.78% of individuals with HBV-related HCC [73]. GOLGA2P10 is upregulated in HCC tissues and cells treated with ER stress inducers (tunicamycin and thapsigargin) [74].…”
Section: Cancers Located In the Abdomen And Bonesmentioning
confidence: 99%
“…39,40 AOC4P had been studied primarily only in tumors. 41 In this study, we first examined the expression of AOC4P in PCOS GCs and this downregulation was subsequently confirmed. Then, we hypothesized that AOC4P might mediate the Our study firstly confirmed the low expression of AOC4P in GCs of PCOS patients.…”
Section: Discussionmentioning
confidence: 85%
“…Some studies had established characteristic lncRNA expression profiles, attempting to use it as diagnostic or prognostic markers for different diseases 39,40 . AOC4P had been studied primarily only in tumors 41 . In this study, we first examined the expression of AOC4P in PCOS GCs and this downregulation was subsequently confirmed.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies have exhibited abnormal expression of pseudogenes in a variety of tumors, such as colorectal cancer, HCC, renal cell carcinoma, and gastric cancer (Chen et (Hu et al 2020). In our work, we found that the pseudogene CTB-63M22.1 has the same mutation frequency and co-expression module as mRNAsi.…”
Section: Discussionmentioning
confidence: 99%